Effect of semi-composted fiber mixtures with soil on growth and disease tolerance in nursery oil palm plants - Garbanzo, Gabriel (2017)
The effect of different composted fiber mixtures from empty bunches with soil for substrate in nursery oil palm plants and its effect on the severity of Foliar Necrosis Complex (CNF) was evaluated in the South Pacific of Costa Rica. Volumetric mixtures of 12, 25, 37 and 50% of composted fiber (C) with Eutrico Inceptisol soil were made. Compacta x Ghana oil palm plants were planted in 20 L bags and arranged in a complete randomized block design comprising 5 treatments and 4 replicates. 85, 127, 176, 219, 261 and 304 days after sowing (dds), plant morphological growth, percentage of CNF severity in leaves, and dry weight of plants were measured, and nutrient uptake was calculated. Apparent bulk density (Dap) and hydraulic conductivity (CH) were also evaluated in the mixtures at 90 and 300 dds. It was found that the 12% fiber with soil mixture showed the lowest percentage of CNF severity and presented the highest nutrient uptake efficiency in comparison to the rest of the treatments. Dap was significantly lower and CH was significantly higher in all mixtures when compared to the control treatment. It can be concluded that 12% composted fiber with 88% soil mixture improved nutrient uptake in plants and increased CNF tolerance in nursery oil palm plants.